Impacts of maternal nutrition on uterine and placental vascularity and mRNA expression of angiogenic factors during the establishment of pregnancy in beef heifers. Issue 2 (1st April 2017) - McLean, K. J.; Crouse, M. S.; Crosswhite, M. R.; Pereira, N. Negrin; Dahlen, C. R.; Borowicz, P. P.; Reynolds, L. P.; Ward, A. K.; Neville, B. W.; Caton, J. S.
Abstract: We hypothesized that maternal nutrient restriction starting at the time of breeding would influence placental vascular development and gene expression of angiogenic factors during the first 50 d of gestation in beef heifers. Commercial Angus crossbred heifers ( n = 49) were maintained on a total mixed ration and supplemented with dried distillers grains with solubles. All heifers were subject to 5-d CO-Synch + CIDR estrous synchronization protocol, AI to a single Angus sire, and randomly assigned to dietary treatments. One half were assigned to control diet (CON) targeted to gain 0.45 kg/d and the remaining half were assigned to restricted diet (RES), which received 60% of CON. Heifers were subjected to ovariohysterectomy on d 16, 34, or 50 of gestation. Utero-placental tissues were obtained from the uterine horns ipsilateral and contralateral to the corpus luteum and separated into maternal caruncle (CAR); maternal endometrium, inter-caruncle (ICAR), and fetal membranes (FM). After collection, all tissues were snap frozen and stored at –80°C. There were no treatment × stage of gestation interactions ( P >0.13) on the mRNA expression of vascular endothelial growth factor ( VEGF ) or endothelial nitric oxide synthase ( eNOS ). Heifers on CON treatment had greater ( P = 0.03) expression of VEGF compared with RES heifers in NP-ICAR. On d 50 expression of eNOS was increased ( P = 0.05) compared with d 16 in P-CAR. Expression of eNOS mRNA was decreased ( P = 0.04) on d 16 compared with d 34 and 50 in CON heifer. Gene expression of eNOS was increased ( P < 0.001) in the pregnant uterine horn compared with the NP uterine horn on d 34 and 50. Expression of eNOS was also increased ( P < 0.003) on d 34 and 50 in the pregnant uterine horn compared with FM. There was a maternal nutritional plane × stage of gestation interaction ( P = 0.01) on the vascular ratio (vascular volume/tissue volume) in maternal tissues. The RES heifers had a greater vascular ratio on d 16 compared with d 34 and 50; whereas, CON heifers had a greater vascular ratio on d 34 compared with d 16 and 50. In the NP uterine horn, there was also an increase ( P = 0.02) in vascular volume of FM from CON heifers compared with FM from RES heifers. We conclude that maternal nutrient restriction did alter both vascularity and mRNA expression of angiogenic factor in utero-placental tissues during the establishment of pregnancy in first parity beef heifers.